The Addams family : the complete second volume [videorecording (DVD)] - Addams, Charles, 1912-1988; Astin, John; Jones, Carolyn, 1930-1983; Cassidy, Ted; Coogan, Jackie, 1914-1984; Weatherwax, Ken, 1955-2014; Loring, Lisa; Blake, Marie, 1899-1978 (MGM DVD., 2006)
The Addams family returns for more creepy capers and hair-raising hilarity, terrifying their neighbors and delighting viewers like never before. Volume 2 features the ghoulish gang in fine form: Gomez runs for mayor, Lurch becomes a pop star, Uncle Fester turns Pugsley into a chimp, and Cousin Itt loses his hair.